Fumigant activity and transcriptomic analysis of two plant essential oils against the tea green leafhopper, Empoasca onukii Matsuda - Tan, Weiwen; Zhang, Ni; Wang, Jinqiu; Pu, Tianyi; Hu, Jifeng; Li, Can; Song, Yuehua (Frontiers in Physiology, 2023)
The tea green leafhopper, Empoasca (Matsumurasca) onukii Matsuda, R., 1952 (Hemiptera: Cicadellidae), is currently one of the most devastating pests in the Chinese tea industry. The long-term use of chemical pesticides has a negative impact on human health, impeding the healthy and sustainable development of the tea industry in this region. Therefore, there is a need for non-chemical insecticides to control E. onukii in tea plants. The essential oils from plants have been identified for their potential insecticidal ability; however, there is a lack of knowledge regarding the effect of plant essential oils on E. onukii and its gene expression. In order to address these knowledge gaps, the components of Pogostemon cablin and Cinnamomum camphora essential oils were analyzed in the present study using gas chromatography-mass spectrometry. The 36-hour lethal concentration (LC50) values for E. onukii treated with P. cablin and C. camphora essential oils were 0.474 and 1.204 μL•mL -1 respectively. Both essential oils exhibited the potential to control E. onukii, but the fumigation activity of P. cablin essential oil was more effective. A total of 2,309 differentially expressed genes were obtained by transcriptome sequencing of E. onukii treated with P. cablin essential oil. Many of these genes were found to contain detoxification genes, indicating that these families may have played an important role when E. onukii was exposed to essential oil stress. We also found differential expression of genes related to redox-related gene families, suggesting the upregulation of genes associated with possible development of drug and stress resistance. This work offers new insights for the prevention and management of E. onukii in the future.